2006
DOI: 10.1189/jlb.0406295
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of MCP-1 increases development of herpetic stromal keratitis by innate immune modulation

Abstract: Chemokines are important chemoattractant inflammatory molecules, but their interdependent network in disease pathogenesis remains unclear. Studies in mouse models have shown that herpetic stromal keratitis (SK) is produced by the consequence of a tissue-destructive immunoinflammatory reaction involving herpes simplex virus type 1 (HSV) infection. Here we found that ocular HSV infection leads to increased expression of monocyte chemoattractant protein-1 (MCP-1), one of the major chemoattractants for immune cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…41 It has been shown that CCL-2/MCP-1 depletion resulted in innate immune modulation and increased corneal inflammation as a result of MIP-2 overexpression. 42 In fact, we found increased amounts of MIP-2/CXCL2 in murine corneas with HSK and AMT. 24 Neutralizing antibodies to MIP-2 suppressed HSV-1-specific DTH and sharply reduced neutrophil accumulation in the ear pinna.…”
Section: Discussionmentioning
confidence: 91%
“…41 It has been shown that CCL-2/MCP-1 depletion resulted in innate immune modulation and increased corneal inflammation as a result of MIP-2 overexpression. 42 In fact, we found increased amounts of MIP-2/CXCL2 in murine corneas with HSK and AMT. 24 Neutralizing antibodies to MIP-2 suppressed HSV-1-specific DTH and sharply reduced neutrophil accumulation in the ear pinna.…”
Section: Discussionmentioning
confidence: 91%
“…NK cell influx in infected tissues is coordinated by chemokines such as CCL2 (18). CCL2 is also upregulated in HSV-1 infected corneas (19). Therefore, we determined the levels of CCL2 in the corneal lysates from both groups of mice on day 2 post-infection.…”
Section: Resultsmentioning
confidence: 99%
“…***P 0.001. angiogenesis was recorded as described previously. 19 In reference to the angiogenic scoring system, the method relied on quantifying the degree of neovessel formation based on three primary parameters: the circumferential extent of neovessels (as the angiogenic response is not uniformly circumferential in all cases), the centripetal growth of the longest vessels in each quadrant of the circle, and the longest neovessel in each quadrant was identified and graded between 0 (no neovessel) and 4 (neovessel in the corneal center) in increments of 0.4 mm (radius of the cornea is 1.5 mm). According to this system, a grade of 4 for a given quadrant of the circle represents a centripetal growth of 1.5 mm toward the corneal center.…”
Section: Clinical Observationsmentioning
confidence: 97%